2020
DOI: 10.1093/eurheartj/ehaa409
|View full text |Cite|
|
Sign up to set email alerts
|

Reduction of hospitalizations for myocardial infarction in Italy in the COVID-19 era

Abstract: Aims To evaluate the impact of the COVID-19 pandemic on patient admissions to Italian cardiac care units (CCUs). Methods and Results We conducted a multicentre, observational, nationwide survey to collect data on admissions for acute myocardial infarction (AMI) at Italian CCUs throughout a 1 week period during the COVID-19 outbreak, compared with the equivalent week in 2019. We observed a 48.4% reduction in admissions for AMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
596
9
25

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 784 publications
(722 citation statements)
references
References 16 publications
61
596
9
25
Order By: Relevance
“…Both patient and system related delays were also observed: time from symptom onset to coronary angiography increased by 39.2%, time from first medical contact to coronary angiography increased by 31.5%, and the STEMI case fatality rate increased (relative risk 3.3) during COVID-19. 3 Possible reasons for avoiding necessary medical care may include fear of contracting COVID-19, as was previously found during the severe acute respiratory syndrome (SARS) outbreak of 2003. 11 Middle East respiratory syndrome (MERS) and SARS both had high levels of transmission in healthcare settings, 12 the memory of which may have reduced health service utilisation during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both patient and system related delays were also observed: time from symptom onset to coronary angiography increased by 39.2%, time from first medical contact to coronary angiography increased by 31.5%, and the STEMI case fatality rate increased (relative risk 3.3) during COVID-19. 3 Possible reasons for avoiding necessary medical care may include fear of contracting COVID-19, as was previously found during the severe acute respiratory syndrome (SARS) outbreak of 2003. 11 Middle East respiratory syndrome (MERS) and SARS both had high levels of transmission in healthcare settings, 12 the memory of which may have reduced health service utilisation during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…As health systems across the world respond to the coronavirus disease 2019 (COVID- 19), there is rising concern that patients with non-COVID-19 emergency conditions are avoiding care. [1][2][3][4] In the Italian Paediatric Hospital Research Network, 12 cases of delayed access to hospital care were reported in 1 week, with 6 cases requiring admission to an intensive care unit and 4 deaths. 1 Parents of these children reported avoiding hospitals for fear of contracting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative virus of COVID-19, with some even reporting being discouraged from attending a hospital by their usual healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 2 summarizes the actual occupancy rate of the ICU beds to date (29 th of March 2020). It is important to note that the occupancy rate is computed considering the number of beds available in each region in 2017 and the number of hospitalized patients affected by COVID-19 and does not take into account patients admitted with other pathologies [33]. As highlighted by the colour, different regions have already saturated the hospital beds ordinarily available in their ICUs (Lombardia, Piemonte, Val d'Aosta, Trento, Bolzano), with other regions worryingly approaching this threshold (Marche, Emilia Romagna, Toscana, Liguria).…”
Section: Impact Of the Covid-19 Outbreak In The Hospital Bed Managemementioning
confidence: 99%
“…[1][2][3] This would inevitably have important consequences especially in conditions such as ST-elevation myocardial infarction (STEMI) in which timely coronary revascularisation is proven to reduce mortality and complications. 4 While there are isolated local and regional level reports that the COVID-19 pandemic is associated with a reduction in both presentations with acute myocardial infarction and percutaneous coronary intervention (PCI) procedures, [5][6][7][8][9] there have been no previous data regarding its impact on national primary PCI rates and practices and whether there have been changes in either procedural or clinical characteristics of patients or their clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%